Síntese de selanil-(hetero)arenos via selenilação da ligação C(sp2)-H promovida por Ácido Tricloroisocianúrico (TCCA) - Granja, Isis Juliane Arantes (2025)
This thesis proposes a sustainable and efficient methodology for the direct selenylation of (hetero)arenes via selective C(sp2)-H bond functionalization, usmg trichloroisocyanuric acid (TCCA) as an oxidizing agent. The goal was to develop a synthetic strategy that eliminates the need for metal catalysts and toxic solvents, aligning with Green Chemistry principies. The methodology involved mild reaction conditions, employing TCCA as the oxidant and ethanol as a green solvent. Various reaction conditions were explored to optimize the selective introduction of organoselenium groups into N-heteroarenes such as imidazo[l,2-a]pyridine, imidazo[2, 1-b ]thiazole, and indole. The experiments yielded impressive results, ranging from 39% to 97%, with an average of 75%. Mechanistic investigations revealed two main pathways for functionalization, with the electrophilic activation of diselenides proving to be the most efficient. The results highlight the methodology's high selectivity and broad functional group tolerance, setting it apart from traditional approaches. Additionally, this strategy enables efficient functionalization of aromatic and heterocyclic substrates without the need for directing groups or metal catalysts, expanding its synthetic scope. The versatility of this approach opens new possibilities for future research in organic chemistry, including the selective modification of 1tconjugated systems and the construction of novel molecular structures. Overall, the findings reinforce the importance of sustainable chemistry in the synthesis of organochalcogen compounds, providing an efficient and environmentally friendly method for obtaining selenylated derivatives with potential applications across various fields of organic chemistry.